The Communication Conflict At The Research And Development Institute - Ayi Doni Darussalam; Djuara Pangihutan Lubis; Dyah Rachmawati Sugiyanto (MediaTor)
This study analyzed organizational conflicts at the Indonesian Institute of Sciences (Indonesian: Lembaga Ilmu Pengetahuan Indonesia (LIPI)) that occurred in 2019. LIPI is the largest research & development institution in Indonesia with the task of promoting sciences. For this reason, the presence of conflicts disturbed its performance. In this study, the researchers applied a qualitative method with a case study approach. Data were collected through semi-structured in-depth interviews and document study. The results indicated that the source of the conflict was the issuance of LIPI Regulation No. 1/2019 concerning the Organization and Work Procedure of LIPI. Besides, the causes were the presence of conflicts of interest related to the struggle for limited resources, different conceptions & goals in managing the organization, and communication barriers. The impacts of the conflict were demonstrations, the emergence of apathy, individualism, and opportunism in some employees, and the delay of internal services. This conflict was resolved through dialogue, mediation, and speeding up the policy implementation process. In this conflict, the Head of LIPI was the actor who had high power and interest, while human resources (in science and technology and its supporting) and non-civil-servant government employees were internal actors who had high interests but weak power.